A targeted amplicon sequencing panel to simultaneously identify mosquito species and Plasmodium presence across the entire Anopheles genus. (19th June 2021) - Makunin, Alex; Korlević, Petra; Park, Naomi; Goodwin, Scott; Waterhouse, Robert M.; von Wyschetzki, Katharina; Jacob, Christopher G.; Davies, Robert; Kwiatkowski, Dominic; St. Laurent, Brandyce; Ayala, Diego; Lawniczak, Mara K. N.
Abstract: Anopheles is a diverse genus of mosquitoes comprising over 500 described species, including all known human malaria vectors. While a limited number of key vector species have been studied in detail, the goal of malaria elimination calls for surveillance of all potential vector species. Here, we develop a multilocus amplicon sequencing approach that targets 62 highly variable loci in the Anopheles genome and two conserved loci in the Plasmodium mitochondrion, simultaneously revealing both the mosquito species and whether that mosquito carries malaria parasites. We also develop a cheap, nondestructive, and high‐throughput DNA extraction workflow that provides template DNA from single mosquitoes for the multiplex PCR, which means specimens producing unexpected results can be returned to for morphological examination. Over 1000 individual mosquitoes can be sequenced in a single MiSeq run, and we demonstrate the panel's power to assign species identity using sequencing data for 40 species from Africa, Southeast Asia, and South America. We also show that the approach can be used to resolve geographic population structure within An. gambiae and An. coluzzii populations, as the population structure determined based on these 62 loci from over 1000 mosquitoes closely mirrors that revealed through whole genome sequencing. The end‐to‐end approach is quick, inexpensive, robust, and accurate, which makes it a promising technique for very large‐scale mosquito genetic surveillance and vector control.